Personalized collection of plasma from healthy donors: A randomized controlled trial of a novel technology‐enabled nomogram. Issue 6 (21st April 2021) - Hartmann, Jan; Ragusa, Michael J.; Burchardt, Elmar R.; Manukyan, Zorayr; Popovsky, Mark A.; Leitman, Susan F.
Abstract: Background: Source plasma is essential to support the growing demand for plasma‐derived medicinal products. Supply is short, with donor availability further limited by the coronavirus disease 2019 (COVID‐19) pandemic. This study examined whether a novel, personalized, technology‐based nomogram was noninferior with regard to significant hypotensive adverse events (AEs) in healthy donors. Study Design and Methods: IMPACT (IMproving PlasmA CollecTion) was a prospective, multicenter, double‐blinded, randomized, controlled trial carried out between January 6 and March 26, 2020, in three U.S plasma collection centers. Donors were randomly assigned to the current simplified 1992 nomogram (control) or a novel percent plasma nomogram (PPN) with personalized target volume calculation (experimental). Primary endpoint was the rate of significant hypotensive AEs. Noninferiority (NI) was tested with a margin of 0.15%. Collected plasma volume was a secondary endpoint. Results: A total of 3443 donors (mean [SD] BMI: 32 [7.74] kg/m 2 ; 65% male) underwent 23, 137 donations (median [range]: 6 [1–22] per subject). Ten significant hypotensive AEs were observed (six control; four experimental), with model‐based AE incidence rate estimates (95% CI) of 0.051% (0.020%–0.114%) and 0.035% (0.010%–0.094%), respectively ( p = .58). NI was met at an upper limit of 0.043% versus the predefined margin of 0.15%. There was no statistical difference between total AEs (all AE types: p = .32). Mean plasma volume collected was 777.8 ml (control) versus 841.7 ml (experimental); an increase of 63.9 ml per donation (8.2%; p < .0001). Conclusion: This trial showed that a novel personalized nomogram approach in healthy donors allowed approximately 8% more plasma per donation to be collected without impairing donor safety.